人工智慧時代醫患關係的“關懷”倫理構建: The “Care” Ethical Construction of the Physician-patient Relationship in the Era of Artificial Intelligence - XIAO, Wei; GAO, Ran; CHEN , Shan (International Journal of Chinese & Comparative Philosophy of Medicine, 2024)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 隨著21世紀以來的科技發展進步，人類正在進入一個“人機物”三元融合的萬物智能互聯時代。人工智慧（AI）和大數據已經對人們對醫患關係的傳統認知提出挑戰。在生命倫理學領域，如何闡釋醫患關係問題已不是簡單的概念討論和爭辯，而關乎到AI時代醫生職業精神的塑造、醫學發展向善的價值導向與實錢，以及醫學人文精神與和諧社會的追求。國内學者一直對醫患關係性質問題爭論不休，美國倫理學家雅克．蒂洛等人也概括出醫患倫理關係的三個形式。然而，這些討論和形式都存在某種程度的不足。儒家和女性主義關懷倫理學都屬於“關懷”倫理，基於這兩種理論資源，醫患關係可以理解為一種關懷關係，並可以通過關係自主性和生命共同體理念進行構建。 The rapid progress of science and technology in the 21st century has ushered humanity into an era characterized by the intelligent interconnectedness of all entities through the tripartite integration of humans, machines, and objects. The emergence of artificial intelligence (AI) and big data has posed challenges to conventional perceptions of physician–patient relationships. Within bioethics discourse, interpreting such relationships is now more important than mere conceptual deliberation, as it can help to shape the professionalism of physicians in an AI-driven age. In addition, such interpretation can align medical development with ethical values aimed at fostering a humanistic spirit within healthcare practices to help build a harmonious society. Domestic scholars have been engaged in debates concerning this issue, and the American ethicist Jacques Paul Thiroux and others have proposed three models for the ethical interactions between physicians and patients. However, these discussions exhibit some limitations. Confucian ethics alongside the feminist ethics of care can contribute to what can be termed “care” ethics. Leveraging these theoretical foundations allows us to perceive physician–patient relations as inherently caring and as able to be cultivated through notions such as relational autonomy within communal living.